Comparison of the 10-year outcomes of cemented and cementless unicompartmental knee replacements: data from the National Joint Registry for England, Wales, Northern Ireland and the Isle of Man - Mohammad, Hasan R (Acta Orthop, 2019)
Background and purpose — Unicompartmental knee replacement (UKR) offers advantages over total replacement but has higher revision rates, particularly for aseptic loosening. The cementless Oxford UKR was introduced to address this. We undertook a registry-based matched comparison of cementless and cemented UKRs. Patients and methods — From 40,552 Oxford UKRs identified by the National Joint Registry for England, Wales, Northern Ireland and Isle of Man (NJR) we propensity score matched, based on patient, surgical, and implant factors, 7,407 cemented and 7,407 cementless UKRs (total = 14,814). Results — The 10-year cumulative implant survival rates for cementless and cemented UKRs was 93% (95% CI 90–96) and 90% (CI 88–92) respectively, with this difference being significant (HR 0.76; p = 0.002). The risk of revision for aseptic loosening was less than half (p < 0.001) in the cementless (0.42%) compared with the cemented group (1.00%), and the risk of revision also decreased for unexplained pain (to 0.46% from 0.74%; p = 0.03) and lysis (to 0.04% from 0.15%; p = 0.03). However, the risk of revision for periprosthetic fracture increased significantly (p = 0.01) in the cementless (0.26%) compared with the cemented group (0.09%). 10-year patient survival rates were similar (HR 1.2; p = 0.1). Interpretation — The cementless UKR has improved 10-year implant survival compared with the cemented UKR, independent of patient, implant, and surgical factors. This improved survival in the cementless group was primarily the result of lower revision rate for aseptic loosening, unexplained pain, and lysis, suggesting the fixation of the cementless was superior. However, there was a small increased risk of revision for periprosthetic fracture with the cementless implant.